The removal of donor anonymity in the UK: the silencing of claims by would-be parents - Turkmendag Brunsnes, Ilke (2009)
From 1 April 2005, UK law was changed to allow children born through gamete donation to access identifying details of the donor. The decision to abolish donor anonymity was strongly influenced by a discourse that asserted the 'child's right-to-know' their genetic origins. Under the current regulation, if would-be parents want to receive treatment in the UK, they have no option but to use gametes/embryos from identifiable donors. For a majority, this also means that they will be on lengthy waiting lists due to the donor shortage. Interestingly, the voice of would-be parents - those who would be most affected by a contraction in donor supply and would carry the burden of informing children of their origins, should they so choose- were not heard during the donor anonymity debate or thereafter.